(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: + To describe the clinical manifestations of hemorrhoid patients treated with a Diode Laser in 108 Military Central Hospital. + To describe the technique and early result of Treatment of Haemorrhoidal Disease by Laser Diode 1470nm Method: Descriptive, case - series study. 59 patients with second and third-degree hemorrhoids treated with Diode Laser 1470nm (Biolitec). Laser energy:10 – 15W, each pulsed shot of 1,2s with 0,6s interval between pulses. Results: The mean age of patients was 42,8 ± 14,3 years. Grade III hemorrhoids was 66,1% as compare with 33,9% of Grade II hemorrhoids. The success rate was 98,3%. The mean operation time was 15,9 ± 4,5 minutes. The mean pain score (VAS) on day 1, day 7, day 14 and 6 weeks after surgery was 3,6 ± 0,9, respectively 1,7 ± 0,7, 1,0 and 0. The mean hospital charge was 1,3 ± 0,9 days. The overall incidence of complications was 13,6%. The mean Hemorrhoidal Disease Symptom Score before and 3 months post-treatment was 8,6 ± 2,3 and 1,0 ± 1,0. Conclusion: Diode Laser 1470nm is safe and effective in treating Grade II and Grade III hemorrhoids.